Results of simulation of performance indicators for the oncological service when introducing innovative technologies for treatment of stage IV lung cancer - S. A. Sterlikov; O. V. Zelenova; S. I. Аbramov; V. M. Danilov; Yu. V. Mikhaylova; N. A. Golubev (Туберкулез и болезни лёгких)
Malignant tumors of the trachea, bronchi, lungs represent a serious medical and social problem. Most cases of cancer of the trachea, bronchus, and lung are detected at stage IV, and therefore, to improve the survival of patients, a new treatment strategy is proposed based on modern data on mutagenesis and receptor status of tumor cells, which has a personalized approach for each specific case. To make managerial decisions about the introduction of innovative drugs, a forecast of expected results is required which should be improved indicators of the State Program On Healthcare Development. It has been found out that the transition to a new strategy for lung cancer chemotherapy will reduce mortality from malignant tumors by 1.2-0.7%, including lung cancer by 3.9%, as well as one-year case fatality by 3% for all malignant tumors, including 15% for lung cancer. At the same time, within 5 years after the introduction of the new strategy for lung cancer treatment, the indicator reflecting the proportion of patients with malignant tumors registered for 5 years or more is expected to decrease, which is related to specific parameters of the calculation method.The authors state that they have no conflict of interests.